Human Emotion In Bruno Major Album (2020): A Psychological Perspective - Dhaly Anugrah Ilahi, Adinda (Universitas Cokroaminoto Palopo, 2026)
This study investigates the representation of human emotions within Bruno Major’s 2020 album, To Let a Good Thing Die, through the lens of literary psychology. While music is a profound medium for expressing the human experience, this specific work has seen limited academic exploration. Utilizing David Krech’s emotional classification, the research aims to identify various emotional types and analyze the psychological meanings embedded in the lyrics. A qualitative descriptive method was applied to five selected tracks: “Nothing,” “Regent’s Park,” “I’ll Sleep When I’m Older,” “To Let a Good Thing Die,” and “Tapestry.” The findings reveal that the album encompasses all four of Krech’s categories, identifying nine distinct emotions such as happiness, sadness, and regret. Happiness and sadness emerge as dominant themes, frequently portrayed through natural metaphors and daily routines. Ultimately, the study concludes that the album serves as a reflective narrative on intimacy, loss, and acceptance, offering a contemporary medium for emotional healing and psychological complexity.